Menciptakan Harmoni di Tengah Konteks Keragaman: Menimba Inspirasi dari Filsafat Levinas - Hidayat, Elvin Atmaja (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
“Harmony” is a condition or situation that every human being is yearning or looking for around the world, as a person-and in the context as a nation. Because, the harmony in society becomes one of the guarantor of economic, social-cultural, and political stability in that society. Harmony also enables people to be develop fully and make them truly happy. However, these days, harmony becomes a “rare” item. Various crimes are increasing in various parts of the world and remove the harmony massively. Apparently, the main cause of these conflicts is the “diversity” of tribes, religions, etc. Emmanuel Levinas, a Jewish philosopher, offers an inspiration to restore the harmonization with his “philosophy of face”. Levinas invites people to look at their neighbours with new perspectives. Harmonization is created, not because of considering the “others” to be the same as ‘me’ (homogeneous), but because the “others” are really different from‘me’ (heterogeneous). For Levinas, the attitude of mutual respect and responsibility for each other is raised up by suchdifference or “absolute otherness”.